Incidencia de infección quirúrgica y factores de riesgo en cirugÃa colorrectal. Estudio de cohorte prospectivo - Javier Páramo-Zunzunegui; Marcos Alonso-GarcÃa; Diego RodrÃguez-Villar; Justina Drewniak-Jakubowska; Pablo Calvo-Espino; Rosa Cuberes-Montserrat; Gil RodrÃguez-Caravaca (Permanyer, 2021)
Objective: The objective was to measure the incidence of surgical site infection (SSI) and identify risk factors, in patients undergoing elective surgery of the colon and rectum. Materials and methods: A prospective cohort study was performed from January 2017 to December 2018. Results: A total of 130 patients were studied. The cumulative incidence of SSI was 12.3%. The 56.25% were superficial wound infections and the 31.25%, organ-space infection. The risk factors significantly associated with SSI were the non-administration of pre-operative oral nutrition, diabetes mellitus, heart disease, symptomatic state at the diagnosis of colorectal cancer (CRC), and ≥ 2 altered nutritional biochemical parameters at diagnosis. After multivariate , risk factors associated with SSI were: non-administration of preoperative enteral nutrition (odds ratio [OR] = 0.27; 95% confidence interval [CI]: 0.07-1.0), DM (OR = 3.0; 95% CI: 0.9-9.9), the heart disease (OR = 4.6; 95% CI: 1.1-18.6), and laparoscopic surgery (OR = 0.28; 95% CI: 0.08-0.97). The average stay was higher in patients with a diagnosis of SSI (11.9 vs. 9.2 days). Conclusions: Independent risk factors for SSI in CRC were the non-administration of pre-operative enteral nutrition, the existence of heart disease, and open surgery.